(untitled) (Medico Legal Update, 2020)
The lesson of physical education is more vulnerable to the problems of attracting attention as it is in a wider area and includes freedom of movement and flexibility in dealing in the classroom and sometimes the distraction in the physical education school increases due to the large number of female students, thus providing the opportunity to practice such behavioral problems, since the practice of sports activity, especially the physical education lesson, is appropriate for free behavior and from it turns into an abnormal behavior as a result of being affected by the family circumstances to which the female students belong, Hence the importance of this research shows that the problems of attracting attention If the professors, educators, and researchers do not work with research to determine it, which leads to female students’ personal and social maladjustment in and outside the school, then when these problems are left without supervision, it may lead to their increase and the difficulty of dealing with them, In addition to the inability of female students to agree in the school, and therefore, a barrier between them and benefiting from the school’s educational and educational services that achieve integrated and balanced growth for all aspects of personality, to qualify them for the right citizenship in line with the goals of society, As for the research methodology, the researcher used the descriptive approach in the survey method to suit the nature of the research problem. As for the research sample, the research community was identified as physical education female teachers in Dhi Qar Governorate for the preparatory stage as shown in table (1) so the number of schools reached (50) schools, while the number Female teachers reached (235) Female teachers. As for the research findings, the most important of them is the scale that was prepared by researchers as a tool to uncover problems of attracting attention in the lesson of physical education for the preparatory stage from the point of view of female teachers. They resort to attract the attention of others With negative behavior.